Effect of seed enhancement treatments on field emergence, flowering behaviour and seed yield of speciality maize - HEENA RASOOL MIR; SUDIPTA BASU; MALAVIKA DADLANI; SUKHBIR SINGH (Seed Research, 2026)
Efficacy of pre-sowing seed enhancement treatments namely hydro, matrix (Pusa hydrogel), halo (KNO,@ 0.3%), bio-priming (fulvic acid @ 0.1% and earth worm-derived compounds: ceolomic fluid, vermiwash), seed treatments (Thiram @3 g/kg of seed, Cruiser @ 4g/kg of seed and Kalisena @ 8g/kg of seed), and magnetic stimulation (1000 G for 2h) singly or in combination were assessed on speciality maize i.e. Quality protein maize ’HQPM-1’, Pop corn ’VL Amber pop corn’, Sweet corn ’Win orange sweet corn’ and common maize ’Parkash’. The results showed significant beneficial effect of seed enhancement treatments on field emergence, speed of emergence, early seedling growth (fresh and dry weight), plant height and seed yield. These treatments advanced flowering by 1-2 days over control. Hydro-priming (17h for 20°C) followed by dry dressing with thiram (3g/kg of seed), halo-priming with KNO, (0.3%) (17h for 20°C), bio-priming with fulvic acid (0.1%) and ceolomic fluid and magnetic stimulation (1000 G for 2h) were more effective in improving field performance and yield of genotypes as compared to control. Among cultivars, Win orange sweet corn and Parkash were more responsive to seed enhancement treatments than HQPM-1 and VL Amber popcorn.